A PHARMACOVIGILANCE STUDY TO ASSESS THE EFFECT OF ADVERSE DRUG REACTION ON PEDIATRIC HEALTH: - ARULRAJA S; THILIP KUMAR GNANADURAI; SUBBULAKSHMI RAMASAMY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study investigated the incidence, demographic and clinical patterns, causative agents, causality, and severity of adverse drug reactions (ADRs) in children. Methods: This study employed a retrospective observational design to investigate ADRs in pediatric patients in the pediatric, ear, nose, and throat, and dermatology departments. ADRs were identified through reports from doctors and nurses, which were based on patient complaints. According to the Institutional Review Board committee’s statement, no ethical committee approval number was required for this study, as it involved only the assessment of symptoms in pediatric patients without any therapeutic interventions. The study was conducted at Chettinad Medical College and Research Institute from March 2011 to February 2012. During this period, 1788 inpatients were monitored for ADRs using a standardized reporting form. The likelihood of ADRs was evaluated using a probability scale, and reactions were classified according to World Health Organization criteria. Results: The study found an ADR incidence rate of 0.73% among 1788 children. ADRs were more common in children aged 6–10 years (61.5%) and males (61.5%). Antimicrobial drugs were the leading cause of ADRs, responsible for 61.5% of cases. The causality assessment showed that 53.84% of ADRs were possible, 23.07% were probable, 7.69% were certain, and 15.38% were conditional. The majority of ADRs (85%) were mild, while 15% were moderate, and none were severe. Conclusion: These findings highlight the importance of monitoring ADRs in children to ensure patient safety and promote safe medication use.